Investigation willingness to have dental treatment during fasting month among muslims in Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi; Sukmasari, Susi; Ali, Aainaa; Abu Zarim, Khairunnisa (International Journal of Multidisciplinary Research and Publications (IJMRAP), India, 2019)
Background and objective: Some authors reported that there was reduce in dental attendance among Muslim patients during fasting month. The objective of this study is to assess the willingness among Muslims in Malaysia to have dental treatment during fasting month. Method: A cross sectional study was carried out on 246 Muslim adults attended primary care clinic in Kuantan, Malaysia. Face-to-face interviews with a structured questionnaire were used to collect sociodemographic profile and to assess the willingness to come for dental treatment during fasting month. We examined association between sociodemographic profile and their willingness to come for dental treatment. Result: Majority participants (70.7%) were unwilling to have dental treatment during fasting month. However, 89% of them were willing to have dental treatment during emergency. Only 11.4% will advise others not to have dental treatment during fasting months. There was no significant association between their willingness to have dental treatment during fasting and the sociodemographic profile. Conclusion: Majority of the Muslims were unwilling to have common dental treatment during fasting but still willing to have it during emergency situation.